Loading monocytes with magnetic nanoparticles enables their magnetic control without toxicity - Mödl, Laura; Carnell, Lucas R.; Stein, Rene; Kerpes, Andrea; Pfister, Felix; Wirthl, Barbara; Wall, Wolfgang A.; Alexiou, Christoph; Janko, Christina (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundWith the help of superparamagnetic iron oxide nanoparticles (SPIONs), cells can be magnetically directed so that they can be accumulated at target sites. This principle can be used to make monocytes magnetically steerable in order to improve tumor accumulation, e.g., for immunotherapy with chimeric antigen receptor (CAR) monocytes. Here, we investigated the loading of monocytic THP-1 cells with SPIONs, analyzed their impact on the viability and cellular reactive oxygen species (ROS) generation and their magnetic enrichment. Finally, we compared and confirmed the experimentally generated magnetic enrichment data with computational simulations.Methods and resultsWhen THP-1 cells were incubated with citrate-coated SPIONs (SPIONCitrate) or citrate-stabilized gold-coated SPIONs (SPIONGold), cells ingested the particles, as determined via transmission electron microscopy and atomic emission spectroscopy. Flow cytometry showed that the particles were biocompatible and produced hardly any ROS. With SPION-loading, cells accumulated in Ibidi flow slides at the edge of a Neodym magnet, where the magnetic field and force were maximal, as calculated by our computational model.ConclusionTHP-1 cells were successfully loaded with SPIONs, which exhibited excellent biocompatibility and provided the cells with magnetic steerability. The computational model predicted the actual magnetic accumulation of the SPION-loaded cells, enabling a more systematic and faster exploration of the design space in the future.